Práticas de letramento informacional de idosos na Biblioteca Pública Epiphânio Dória - Santos, Melânia Lima (2020)
Currently, societies are very concerned about human aging, especially with regard to the biopsychosocial changes presented in old age. These changes can impact the quality of life of the elderly, presenting themselves in a negative or positive way. Negative, when they suffer from age-related issues, such as memory loss, social exclusion, disease onset; positive, when they accept their condition and try to adapt to the modern way of life, such as stating to read, to access to knowledge through different information resources, which stimulate them mentally, leading them to the recognition of their identity. This dissertation presents Information Literacy (LI) from the perspective of Librarianship and Information Science, with people from the Third Age who frequent use the space of the Epiphânio Dória Public Library, in Aracaju/SE. This study is justified because its theme is not discussed enough in scientific studies in Brazil until now. It aims at analyzing the process of information literacy through the LI practices of the elderly public that works and frequents the referred library. The method used for the development of this work is inductive, and its qualitative approach is exploratory and applied in nature. As for the methodology, the research is characterized as an empirical scientific investigation, in which the planned actions were designed to answer questions about the problem raised in a social reality. As for the data collection instrument, the work is supported by the bibliographic analysis and semi-structured questionnaires, with open and closed questions, applied online. For theoretical support, works by specialists were used, in addition to legally based documents. As a product for the Professional master’s degree, an informative and educational booklet was produced in LI, which aims to support the elderly in their daily practices regarding the use of information in libraries, realizing that learning is a benefit for yhe elderly, since, by using the information, he will work harder on his mind, he will know how to salve his problems and difficulties more quickly and above all, he will be happier. I came to the conclusion that the LI is an important ally in the learning process of the elderly who use public libraries, enabling access to information and contributing to the well-being of this particular audience.